Church, State, and Culture: On the Complexities of Post-soviet Evangelical Social Involvement - Lina ANDRONOVIENE; Parush R. PARUSHEV (Богословські роздуми: Східноєвропейський журнал богословʼя)
Taking a lead from tragic experiences in Slavic-speaking immigrant communities in the United States, the authors take a closer look at the historical background and theological presuppositions underlying the social passivity of post-Soviet evangelicals. Its roots are found in the seclusion of their communal life under the suppression of religious communities by the Soviet government. Using insights from the theological tradition of the Radical Reformation, current attitudes and forms of Christian living of the evangelical communities in the former Soviet Union are defined in terms of convictions and beliefs. An attempt is made at a holistic assessment of the resources needed to change the existing attitude toward social involvement. The resources are sought in the wider Christian tradition, as well as in the practice of the Sermon on the Mount. Social involvement is understood by the authors as a wider set of practices including presence, involvement, and extension of fellowship to persons and communities outside the church.